Mitigating climate change with financial investments: exploring sustainable investment strategies in a novel experimental investment paradigm - Hulda Karlsson-Larsson; Arvid Erlandsson; Joakim Sandberg; Daniel Västfjäll (Judgment and Decision Making)
Sustainable financial investments play a role in mitigating climate change. With this research, we explored how decision-makers use three investment strategies illustrating different primary motives: (1) money maximization (economic self-interest), (2) exclusion (not personally harming the environment), and (3) inclusion (helping the environment most efficiently). The relative use of these strategies was tested within a novel investment paradigm, aiming to artificially create a trade-off between financial payoffs (money maximization), environmental purity (exclusion), and environmental impact (inclusion). We recruited 1422 participants online and let them make ten consecutive investment choices, with incentivized outcomes, both monetary (i.e., potential bonus payment) and environmental (i.e., number of trees planted). We tested the change in investment choices using a between-subject design with four conditions, a control, and one default condition for each investment strategy. The three strategies were chosen about equally often in the control condition, but we find that this investment pattern could be altered by a default intervention. Preliminary evidence suggests that participants primarily using the exclusion and inclusion strategies differ in their moral reasoning. Utilitarianism better predicted the inclusion strategy, whereas high self-importance of moral identity better predicted the exclusion strategy.